New teaching strategies in Histology. How to stimulate students' interest and learning capacity? - López-Villodres, Juan Antonio; Sánchez-Varo, Raquel María; Escamilla-Sánchez, Alejandro; Bermúdez-Flores, Diego Teófilo (My University, 2023)
Teaching, in general and specifically in medical schools, is exposed to the use of new methodologies adapted to current times offering diverse possibilities to meet the students needs. Virtual environments, artificial intelligence (AI) and countless digital content open up the possibilities of establishing new teaching strategies. Nevertheless, there are many other tools to arouse students’ interest and find a direct and attractive application of the contents. Histology is an extensive subject that students generally find arid and do not associate with applicability in their future professional development. In order to motivate the student body, our area included a novel section during the development of the classes that connected the theoretical contents to clinical aspects: “From Histology to Medicine”. In this section, we associate histological alterations with specific clinical cases of diseases. Moreover, clinical cases are introduced whenever there is a need to highlight the basic aspects of histological structures in order to diagnose functional alterations that justify the appearance and/or the disease development. We also consider the need to update the evaluation systems, emphasizing that final test should not define the evaluation of knowledge acquisition by the students.. Ideally, the students should become aware of their learning process as a continuum as well. To this aim, we have implemented activities for the continuous evaluation of students, including both face-to-face (theoretical classes, practices and seminars) and remote tests carried out through the virtual campus. Among all these evaluation activities, we have included tests designed to work in groups of 4-5 students that have to debate and agree on the questions raised. In addition, we encourage the students to express their doubts about the contents. Finally, we proceed to a reasoned correction with all the participants to make them completely aware of their own learning process.
Keywords: Histología - Estudio y enseñanza superior; Investigación docente; Enseñanza - Innovaciones; Teaching; New methodologies; Histology; Learning process